Applying the theory of planned behavior to adolescents' acceptance of online friendship requests sent by strangers. Issue 4 (November 2016) - Heirman, Wannes; Walrave, Michel; Vermeulen, Anne; Ponnet, Koen; Vandebosch, Heidi; Hardies, Kris
Highlights: The majority of adolescents have at least one unknown person as friend on SNSs. Subjective norm is the most important determinant of accepting strangers as friends. Prevention strategies of random friending should incorporate subjective norm. Adolescents with high bonding social capital tend to share a more negative attitude. Adolescents with high bridging social capital tend to share a more positive attitude. Abstract: Drawing on a survey conducted among 1743 pupils in 16 Belgian secondary schools, this study applies an extended theory of planned behavior (TPB) to adolescents' acceptance of friendship requests sent by online strangers on social network sites (SNSs). As demonstrated in the literature, random friending on social networking sites can heavily impact adolescents' safety online. Results yielded by means of Structural Equation Modeling show that the subjective norm with regard to the acceptance of strangers as SNS friends is the most important predictor, followed by PBC and attitude. Bonding social capital (an individual's disposal of strong, intimate ties) is negatively associated with attitude and subjective norm, whereas bridging social capital (an individual's disposal of weak, superficial ties) is positively associated with the three TPB antecedents.